2009
DOI: 10.4103/0970-938x.54857
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of serum myeloperoxidase activity in type 2 diabetes and diabetic nephropathy

Abstract: Inflammatory burden is high in End Stage Renal Disease (ESRD) patients. In Diabetic ESRDpatients, the balance between pro-and anti-oxidant activities is shifted towards an oxidative stress. Myeloperoxidase (MPO), a bactericidal enzyme plays an active role in induction and evolution of the endothelial dysfunction associated with Type 2 Diabetes Mellitus (DM). However, whether MPO can serve as a marker in diabetic ESRD patients is doubtful. Hence, the present study was undertaken. The Fasting Blood Glucose (FBG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Myeloperoxidase produced by circulating neutrophils plays an important role in both processes of inflammation and oxidative stress [28]. The current study found significantly higher MPO activities in T2D patients, as observed previously [29], suggesting that it might contribute to the enhanced oxidative stress through the generation of ROS.…”
Section: Discussionsupporting
confidence: 87%
“…Myeloperoxidase produced by circulating neutrophils plays an important role in both processes of inflammation and oxidative stress [28]. The current study found significantly higher MPO activities in T2D patients, as observed previously [29], suggesting that it might contribute to the enhanced oxidative stress through the generation of ROS.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that oxidative stress in T2D patients is also associated with elevated serum and leukocyte levels of myeloperoxidase (MPO) [111][112][113][114]. Using some of our elderly T2D subjects, we have found a strong inverse relationship between RBC Mg 2+ and MPO content (P<0.01) (unpublished findings).…”
Section: Roles Of Mg In Membrane Peroxidation and Generation Of Reactive Oxygen And Nitrogen Species In T2d: Relation To Angiogenesis Andsupporting
confidence: 52%
“…Using some of our elderly T2D subjects, we have found a strong inverse relationship between RBC Mg 2+ and MPO content (P<0.01) (unpublished findings). MPO is one of the most aggressive oxidants of ROS which usually results in elevated serum levels of hypochlorite (OCl -) which are found in T2D patients [112][113][114][115][116][117][118]. We have reported that OCl -, just like the other ROS, can promote constriction of blood vessels [119][120][121][122][123][124].…”
Section: Roles Of Mg In Membrane Peroxidation and Generation Of Reactive Oxygen And Nitrogen Species In T2d: Relation To Angiogenesis Andmentioning
confidence: 99%
“…The activity of MPO, an abundant enzyme of neutrophils, was assessed as previously described 29 with minor modification. Briefly, 1 mL of the serum was mixed with 1 mg of hexadecyltrimethylammonium bromide (HTAB).…”
Section: Mpo Measurementmentioning
confidence: 99%